Transforming Scientific Publication Management in the Era of Disruption: SmartPLS Approach in Innovation and Efficiency Analysis - Ginting Munthe, Rusli; Aini, Qurotul; Lutfiani, Ninda; Van Persie, Iky; Ramadan, Ahmad (Pandawan, 2024)
In the era of technological disruption, scientific publication management faces the challenge of adapting to innovation and increasing efficiency. This research examines the transformation of scientific publication management using the Par- tial Least Squares Structural Equation Modeling (PLS-SEM) method via Smart- PLS. The main variables analyzed include Technology Adaptation (AT), Editorial Process Flexibility (FPE), Digital Platform Integration (IPD), Management Efficiency (EM), and Publication Innovation (IP). Data was collected from an online survey filled out by journal managers, editors, and researchers and in- depth interviews with experts in scientific publications. The results of the Smart- PLS analysis show that Technology Adaptation (AT) has a significant influence on Management Efficiency (EM) and Publication Innovation (IP). Editorial Pro- cess Flexibility (FPE) also increases Publication Innovation (IP). Meanwhile, Digital Platform Integration (IPD) has been proven to strengthen the relationship between technology adaptation (AT) and management efficiency (EM). These findings demonstrate the importance of adaptation to new technologies, flexi- bility in editorial processes, and integration of digital platforms in increasing efficiency and innovation in scientific publication management. This research makes an essential contribution to the scientific publication management liter- ature by integrating the SmartPLS approach. These findings can help journal managers, editors, and researchers formulate effective strategies to face chal- lenges in the era of disruption.